Determinants Of Stunting Among Toddlers: A Systematic Literature Review - Hesteria Friska Armynia Subratha; Km Tri Sutrisna Agustia (WMJ (Warmadewa Medical Journal), 2024)
Stunting remains a significant public health challenge in Indonesia, with a prevalence of 24.4%, according to the 2021 Indonesia Nutrition Status Survey (SSGI). This high rate indicates the country's ongoing struggle to meet its 2024 target of reducing the stunting rate to 14%. Stunting, characterized by impaired growth and development due to chronic malnutrition, is influenced by various socioeconomic, environmental, and biological factors. Understanding these factors is essential for developing effective intervention strategies. This systematic literature review synthesizes current evidence on the determinants of stunting among toddlers in Indonesia, providing insights that can guide public health policies and programs. Using the PRISMA methodology, we comprehensively searched peer-reviewed articles published between 2018 and 2022 from databases such as Google Scholar and PubMed. The studies indicate that stunting is influenced by a complex interaction of factors, including maternal education, household income, sanitation practices, healthcare access, and the child’s age, gender, and health status. Notably, maternal education and household socioeconomic status emerge as critical determinants. The findings emphasize the need for multi-sectoral, community-based interventions that integrate these determinants. In conclusion, addressing these factors through integrated, community-based strategies is crucial for reducing stunting rates and improving child health outcomes in Indonesia.